Fortalecimiento De La Estrategia Reto Saludable En La Comunidad Académica De La Universidad Antonio Nariño - Tesillo Bolaño, Claribeth Julieth (Universidad Antonio Nariño, 2023)
In the country, in accordance with the provisions of Decree 4108 of 2011, the Ministry of Labor is responsible for formulating policies and programs in the areas of occupational health and occupational medicine.